Rola środowiska przyrodniczego w rozwoju zrównoważonym w opinii przedstawicieli samorządu terytorialnego - Grzebyk, Bogumiła (The Self-Government Activity For Natural Environment in Sustainable Development, 2009)
The analysis of a survey conducted in communities with less favoured areas (LFA) of 3 voivodships (małopolskie, śląskie, podkarpackie), among 89 self-government activities is presented in the paper. The respondents had been evaluating the meaning of natural environment in sustainable development. The survey result is that elements of natural environment are the main factors of socio-economic development. Environment protection causes many problems in realizing the community development strategy but large percentage of them undertook working just in this direction between 2000 and 2007. About 80% of communities invested in sewages cleaning, the next was ecological education and wastes segregation. Environment investment monitoring and dangerous wastes recycling were undertaken on a smaller scale. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 578-584